Avaliação dos efeitos antinociceptivo e anti-inflamatório de hidrazonas obtidas por síntese - Medeiros, Maria Alice Miranda Bezerra (2021)
This doctoral thesis is divided into two chapters. The first chapter deals with the evaluation of the antinociceptive and anti-inflammatory effects of hydrazone derivatives and their possible mechanism of action. Several tests were carried out, among them the abdominal contortions induced by acetic acid and the formalin test (using pharmacological blockers to investigate the mechanism of action). It was observed that all hydrazones have an antinociceptive effect and act peripherally. H5 showed better antinociceptive potential, inhibiting 78.92% (20 mg/kg) and 100% (40 mg/kg) of nociception in the second phase of the formalin test. The H5 signaling pathway involves the opioid and nitrergic systems, in addition to the anti-inflammatory effect in leukocyte migration tests in the peritoneal cavity, carrageenan-induced paw edema, and histamine-induced paw edema. Docking demonstrated that H5 inhibits COX-2 in a similar way to meloxicam. In addition, H5 had an adequate pharmacokinetic profile. Therefore, it is a strong candidate asan antinociceptive and anti-inflammatory drug. The second chapter involves the antinociceptive effect of LASSBio-2012. Antinociceptive activity was assessedthrough abdominal contortion tests induced by acetic acid and formalin (using pharmacological blockers). LASSBio-2012 exhibited antinociceptive potential peripherally.In the second phase of the formalin test, it inhibited 50.38% and 65.00% (20 mg/kg and 40 mg/kg, respectively). Its mechanism of action demonstrated a possible involvement of the opioid system. After docking, interactions with delta and mu-opioid receptors were observed and its pharmacokinetic profile was moderate. Therefore, LASSBio-2012 is a candidate for a new antinociceptive drug.